Lactobacillus reuteri SBC5-3 suppresses TNF-α-induced inflammatory responses via NF-κB pathway inhibition in intestinal epithelial cells - Chen, Shiyu; Hu, Tiannian; Xu, Le; Li, Jiqin; Liu, Chen; Zeng, Bangquan; Lin, Qiuye; Cao, Zhenhui (Frontiers in Microbiology, 2025)
The widespread misuse of antibiotics in livestock production has raised growing concerns about antimicrobial resistance and residue contamination. These challenges have led to global restrictions on the use of antibiotic growth promoters (AGPs). However, the ban on AGPs has made the management of intestinal inflammation significantly more difficult, highlighting the urgent need for safe and effective alternatives. Lactic acid bacteria (LAB), known for their immunomodulatory properties, have emerged as promising candidates, though their anti-inflammatory mechanisms remain poorly understood. This study investigated the anti-inflammatory effects and underlying molecular mechanisms of a porcine-derived Lactobacillus reuteri (L. reuteri) strain, SBC5-3. Using tumor necrosis factor-alpha (TNF-α)-induced inflammatory models in the HT-29 cells, we employed RNA sequencing (RNA-seq) combined with Western blot analyses to systematically explore the modulation of inflammatory signaling pathways. RNA-seq demonstrated that L. reuteri SBC5-3 downregulated 9 out of 14 TNF-α-induced genes associated with the TNF and/or nuclear factor kappa B (NF-κB) signaling pathways, including BIRC3, PTGS2, CCL20, TNFAIP3, LTB, CXCL1, CXCL10, IL-8, and CSF1. Specifically, L. reuteri SBC5-3 downregulated key genes in the NF-κB pathway, such as TAK1, IKKα, and NFKB1, while upregulating NFKBIA. Concurrent transcriptional suppression occurred in mitogen-activated protein kinase (MAPK) signaling pathway components ERK and JNK. Western blot analysis further confirmed attenuation of phosphorylation involving TAK1, IKKα/β, and IκBα following SBC5-3 treatment. The collective data demonstrate that immunomodulation mediated by L. reuteri SBC5-3 involves inhibiting IκBα degradation, which is known to be essential for the nuclear translocation of the p50/p65 heterodimer, thereby suggesting inhibition of TNF-α-induced NF-κB nuclear translocation. These results position L. reuteri SBC5-3 as a viable therapeutic agent for inflammation modulation through targeted intervention in NF-κB and MAPK signaling pathways.